Case Report: Autoimmune Lymphoproliferative Syndrome vs. Chronic Active Epstein-Barr Virus Infection in Children: A Diagnostic Challenge - Szczawińska-Popłonyk, Aleksandra; Grześk, Elzbieta; Schwartzmann, Eyal; Materna-Kiryluk, Anna; Małdyk, Jadwiga (Frontiers in Pediatrics, 2021)
Autoimmune lymphoproliferative syndrome (ALPS) is a disorder characterized by a disruption of the lymphocyte apoptosis pathway, self-tolerance, and immune system homeostasis. Defects in genes within the first apoptosis signal (FAS)-mediated pathway cause an expansion of autoreactive double-negative T cells leading to nonmalignant lymphoproliferation, autoimmune disorders, and an increased risk of lymphoma. The aim of the study was to show the diagnostic dilemmas and difficulties in the process of recognizing ALPS in the light of chronic active Epstein-Barr virus (CAEBV) infection. Clinical, immunological, flow cytometric, biomarkers, and molecular genetic approaches of a pediatric patient diagnosed with FAS-ALPS and CAEBV are presented. With the ever-expanding spectrum of molecular pathways associated with autoimmune lymphoproliferative disorders, multiple genetic defects of FAS-mediated apoptosis, primary immunodeficiencies with immune dysregulation, malignant and autoimmune disorders, and infections are included in the differential diagnosis. Further studies are needed to address the issue of the inflammatory and neoplastic role of CAEBV as a triggering and disease-modifying factor in ALPS.